Eksperimen Difraksi Fresnel dengan Gelombang Mikro Pada Penghalang Sisi Lurus - G. Budijanto Untung (Widya Mandala Surabaya Catholic University, 2014)
Research has been carried out about the behaviour of the micro wave when it passed the obstacle to the straight side in Fresnel diffraction. In this research the micro wave evidently crept in the straight direction and omnidirection. This condition, however, was not suitable to be applied in Fresnel diffraction to the obstacle to the straight side. As a result, there was some deviation between the results of the analysis of the data and the theory-based calculation to determine the relative intensity in a certain point by the detector/the micro wave recipient. According to the theory-based calculation, the result of the relative intensity of I/I0 in the P point that was in the geometric shadow bank was 0.25 whereas the result that were received from the analysis of the data was 0.012298. The deviation was 0.238. When the micro wave recipient was placed in the position l of 6 cm, there was evidently some deviation between the theory-based calculation and data-based calculation. The theory-based caculation yielded 0.494554 whereas the data-based calculation arrived at 0.047892. The deviation was 0.4467